2017
DOI: 10.1001/jamainternmed.2017.5073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Promoting High-Quality Staff Interactions on Fall Prevention in Nursing Homes

Abstract: IMPORTANCE New approaches are needed to enhance implementation of complex interventions for geriatric syndromes such as falls.OBJECTIVE To test whether a complexity science-based staff training intervention (CONNECT) promoting high-quality staff interactions improves the impact of an evidence-based falls quality improvement program (FALLS). DESIGN, SETTING, AND PARTICIPANTSCluster-randomized trial in 24 nursing homes receiving either CONNECT followed by FALLS (intervention), or FALLS alone (control). Nursing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…In the present study, the learning modules developed to support the trial will address the education resource issue. The train-the-trainer model and coaching for Site Champions are crucial intervention components that were previously reported in a successful evidence-based quality improvement study [ 40 ]. The present study has adapted these components, but emphasizes leadership for Clinical Mentors and Site Champions in the intervention context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the learning modules developed to support the trial will address the education resource issue. The train-the-trainer model and coaching for Site Champions are crucial intervention components that were previously reported in a successful evidence-based quality improvement study [ 40 ]. The present study has adapted these components, but emphasizes leadership for Clinical Mentors and Site Champions in the intervention context.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational support through investing time and budget in staff development is viewed as a prerequisite for successful quality improvement [ 40 , 41 ]. In the present study, the in-kind contributions made by participating nursing homes to support the time the Clinical Mentor and Site Champions spend on the intervention is evidence of organizational support.…”
Section: Discussionmentioning
confidence: 99%
“…Informed by social constructivist and learning theories and complexity science, which describe learning as a social process drawn from engaged interactions and information flow, CONNECT is a bundle of interaction-oriented activities designed to supplement implementation efforts by promoting team function and readiness for change [ 50 , 56 61 ]. CONNECT was originally developed for fall prevention in nursing homes and has been associated with improvements in communication and participation in decision-making among clinical staff, as well as resident outcomes [ 51 , 62 , 63 ]. As with REP, CONNECT’s design is suitable for rollout in various contexts and phases of implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Implementation of evidence-based practices to prevent falls is essential to decrease the incidence and injuries associated with falls. While multifaceted programs have demonstrated some degree of efficacy [18], other attempts suggest that implementation of evidence-based fall prevention practices remain elusive [19]. A recent implementation study of a nurse-led fall prevention program suggested that enablers to fall prevention included education, training, and improvements in implementation leadership [20].…”
Section: Introductionmentioning
confidence: 99%